(untitled) (Journal of the Management Sciences, 2024)
Information Asymmetry (IA) is crucial to the performance of business entities. Universally, the firm particularly insurance flourishes when information asymmetry (IA) is curtailed to a manageable level. Information asymmetry encourages insider dealings. Activities of insider dealings reduce investors’ confidence, worsen the public’s fear, and impede insurance firms’ performance. Existing studies that evidence the effects of information asymmetry on the performance of insurance firms in Nigeria are rare.Thus, this study examined the effects of information asymmetry on the performance of insurance firms in Nigeria, the country with the largest economy in Africa. The study adopted the purposive sampling technique to select 28 firms quoted in the Nigerian Exchange Group. Data were collected from the annual financial report of firms for the period 2007 to 2022 which were analysed by means of the system generalized method of moments (GMM). Divulgence variance was employed to measure information asymmetry while performance was represented by investment income. Findings showed that information asymmetry significantly inhibits the performance of insurance firms in Nigeria. The study recommends that insurance regulators should enforce full disclosure of all aspects of insurance operations and make them accessible to public consumption. This measure will promote business transparency, stimulate investors’ interest, and improve penetration as well as increase the performance of insurance firms.